From Monologue to Dialogue Interpreting Social Constructivism with Bakhtinian Perspective - Mishra, Rishabh Kumar (JOURNAL OF INDIAN EDUCATION, 2015)
At present it is a well established idea that the construction of knowledge is a process of co-construction of meanings through participation in socially negotiated and discursive activity. The pedagogic translation of this idea owes its root to Vygotskian perspective of development and learning. It envisages teaching-learning as a dialogic process. However it is identified that the idea of dialogue as used by proponents by social constructivist theorist is limited to its methodological implications as a pedagogic tool. The present paper argues that dialogue is not a pedagogic tool rather it is an ontological construct. Against this backdrop the paper argues that for developing a substantial theory of social constructivist pedagogy Bakhtin’s ideas can be deployed. The paper elaborates the vistas of Bakhtin’s idea of dialogue. Further with the help of this elaboration it tries to interpret the epistemological assumption of social constructivist approach to learning. This understanding will enable us to see the agency and the voices of individuals in teaching-learning process. Drawing upon the Bakhtinian perspective, the last section of the paper discusses tenets of dialogic pedagogy which help us to transform the pervasive monologic discourse into dialogic discourse.